![Аетий](https://sproshu.net/uploads/ava/2/ava11252.jpg)
Аетий
6 год назад
Решите уравнение:
(5x-1)(x+2)+3(x-4)(x+4) = 2(2x+3)²-8
Дам 15 баллов!Срочно!❤
ОТВЕТЫ
![Феодорович](https://sproshu.net/uploads/ava/3/ava1963.jpg)
Феодорович
Jul 1, 2019
5x^2 + 10x - x - 2 + 3(x^2 - 16) = 2(4x^2 + 12x + 9) - 8
5x^2 + 9x - 2 + 3x^2 - 48 = 8x^2 + 24x + 18 - 8
8x^2 + 9x - 50 = 8x^2 + 24x + 10
9x - 50 = 24x + 10
9x - 24x = 50 + 10
- 15x = 60
x = - 60/15
x = - 4
5x^2 + 9x - 2 + 3x^2 - 48 = 8x^2 + 24x + 18 - 8
8x^2 + 9x - 50 = 8x^2 + 24x + 10
9x - 50 = 24x + 10
9x - 24x = 50 + 10
- 15x = 60
x = - 60/15
x = - 4
220